Thermal hydraulic assessment on the full banana model of COOL blanket for CFETR - Kecheng Jiang; Lei Chen; Long Chen; Xuebin Ma; Qiuran Wu; Xiaoman Cheng; Juancheng Yang; Xuan Zheng; Nianmei Zhang; Mingjiu Ni; Songlin Liu (Nuclear Fusion, 2024)
The Supercritical Carbon Dioxide (S-CO _2 ) cOoled Lithium-Lead (COOL) blanket is under development for Chinese Fusion Engineering and Test Reactor. The thermal hydraulic assessment plays an important role for the comprehensive performance evaluation on the fusion blanket among the multi-physics fields. As the fusion reactor will enter into the engineering construction stage, it is important to study the thermal hydraulics performance on basis of the full model. Because it can accurately check the heat removal capability and thermoelectricity conversion efficiency, as well as provide essential input for the other physical fields. In this demand-driven, the analyses and optimization on the cooling system are put into priority on basis of the full banana model, including the manifold design and inlet/outlet pipes locations. Finally, the coolant pressure drop is highly reduced and the mass flow distribution becomes much more uniformly. For the S-CO _2 , 82.3% of the total mass flow rate is distributed into the key component first wall, and this is beneficial to face the high radiation heat flux. Besides, under different level of heat flux, the required total mass flow rate and pressure drop are obtained on premise that the coolant has enough ability to safely remove the heat away. For the Lead–Lithium (PbLi), the distribution of mass flow rate is designed as ‘ladder’ shape to adapt the unevenly spatial distributed nuclear heat along the radial direction, and the ratio is 8:2:1. Furthermore, the first law of thermodynamics is adopted for the trade-off analysis, which converts the total pressure drop of the two coolants into the pumping power, and it occupies only 1.3% of the total thermal power. This provides accurate and valuable data for the primary and secondary loop design, as well as the economic assessment on the fusion reactor. Finally, the Two Dimensional thermal hydraulic model containing the detailed layouts of different materials is used to study the coupling heat transfer effects between PbLi and S-CO _2 , as well as the MagnetoHydroDynamics (MHD) effects. The boundary conditions are derived from the results of full banana model, and the results show that the temperature of all materials is not exceeding the upper limits.